P71 Impact of national optimal lung cancer pathway – can we meet the 28 day standard by 2020?. (December 2018) - Kutubudin, F; Robinson, R; Deus, P; Hughes, K; Wight, AG
Abstract : Introduction and objectives: The relationship between early cancer stage and patient outcome is well recognised. It is suggested that streamlined diagnostic pathways could improve this. UK cancer targets are being redefined by publication ' Achieving World Class Cancer Outcomes'. This includes the target of 95% of patients being definitely diagnosed or excluded of cancer and the results communicated to the patient within 28 days by 2020. The National Optimal Lung Cancer Pathway (NOLCP) was published in 2017 defining a timed framework for lung cancer investigation to meet this goal. WUTH introduced an IT driven local version of the NOLCP in October 2017. Using radiology requests from primary care it is a paperless system linking primary care with secondary care radiology, respiratory and outpatient booking services (including endoscopy). A daily consultant virtual clinic forms diagnostic plan from CT scan (day 0), all further diagnostic investigations are pre-arranged (including PET) and where required first method of contact is telephone communication from lung CNS. Information is linked real time to primary care. Methods: Post NOLCP implementation comparison study of pathway timescales over 3 months (January- March 2018) with 3 month baseline September-November 2014 (traditional one-stop clinic) Results: Total patients- 210, 69/210 triage to cancer OPD, 61/210 discharged to primary care, 70/210 downgraded with cancer excluded, 4 referred to other tumour group. Those triaged to cancer clinic 34/69 (49%) confirmed lung cancer, 11/69 (16%) other malignancy, 24/69 benign (total 65% conversion to malignancy). Time from virtual review to formal cancer OPD- mean 5.8 days (target 5 days). Time Flagged CXR (or CT request) to MDT discussion (target 21 days)- 23.9 days (median 22), comparison 2014–38.9 days (median 32). 85% patients informed of treatment plan within 28 days (2014%–39%) Conclusion: Three months following adoption of electronic trackable NOLCP and virtual clinic we have seen shortened diagnostic timeframe by average of 15 days and are on target to meet the 95% target by 2020. We are now completing real-time audit for areas of delay. We feel that 28 day target is achievable even outside tertiary centers.